2018
DOI: 10.1002/ana.25343
|View full text |Cite
|
Sign up to set email alerts
|

Human pegivirus‐1 associated leukoencephalitis: Clinical and molecular features

Abstract: Etiologic diagnosis is uncertain in 35% to 50% of patients with encephalitis, despite its substantial global prevalence and disease burden. We report on 2 adult female patients with fatal leukoencephalitis associated with human pegivirus‐1 (HPgV‐1) brain infection. Neuroimaging showed inflammatory changes in cerebral white matter. Brain‐derived HPgV‐1 RNA sequences clustered phylogenetically with other pegiviruses despite an 87‐nucleotide deletion in the viral nonstructural (NS)2 gene. Neuropathology disclosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…While the actual target cell of the virus is still a mystery, the virus can be detected in natural killer, T and B cells, and in monocytes in chronically infected individuals, suggesting a tropism of the virus for those cell types . The virus has also been implicated is encephalitis of unknown origin with Balcom et al reporting two cases of fatal leucoencephalitis associated with HPgV‐1 brain infection in 2018 . Brain‐derived RNA from the two patients (post‐mortem) contained HPgV‐1 sequences, that were not been identified in white matter samples from over 65 age‐ and sex‐matched control patients with other diseases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the actual target cell of the virus is still a mystery, the virus can be detected in natural killer, T and B cells, and in monocytes in chronically infected individuals, suggesting a tropism of the virus for those cell types . The virus has also been implicated is encephalitis of unknown origin with Balcom et al reporting two cases of fatal leucoencephalitis associated with HPgV‐1 brain infection in 2018 . Brain‐derived RNA from the two patients (post‐mortem) contained HPgV‐1 sequences, that were not been identified in white matter samples from over 65 age‐ and sex‐matched control patients with other diseases .…”
Section: Discussionmentioning
confidence: 99%
“…The virus has also been implicated is encephalitis of unknown origin with Balcom et al reporting two cases of fatal leucoencephalitis associated with HPgV‐1 brain infection in 2018 . Brain‐derived RNA from the two patients (post‐mortem) contained HPgV‐1 sequences, that were not been identified in white matter samples from over 65 age‐ and sex‐matched control patients with other diseases . Another study from 2018 by Fama et al found an association between the presence of HPgV‐1 and the risk of developing lymphoma, and suggested a twofold risk of developing lymphoma with HPgV‐1 viraemia .…”
Section: Discussionmentioning
confidence: 99%
“…HpGV-1 is also reported in association with leukoencephalitis causing inflammatory variation in the cerebral brain. RNA sequences of the virus obtained from the brain resulted in linkages with other Pegiviruses despite deleting 87 nucleotides from the NS2 gene [ 16 ]. Cases of early stages for lymphoma are treated by radiation therapy, although patients exhibiting stage 3 and 4 are prescribed chemotherapy, immunotherapy, and radio immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, hepatitis C virus (HCV) causes a disease that damages the liver [2]. Human pegivirus-1 (HPgV-1), causes human encephalitis [3] as well bovine viral diarrhea (BVDV), a long-known cause of major losses in livestock [4]. Flaviviridae also houses viruses known to cause neglected tropical diseases of the genus Flavivirus, which comprises over 100 different pathogens including notable viruses such as dengue (DENV), West Nile (WNV), yellow fever (YFV), and Zika (ZIKV) [5].…”
Section: Introductionmentioning
confidence: 99%